ANALISIS PENGGUNAAN SIMLALA DALAM PROSES PENERBITAN DOKUMEN PERSETUJUAN KEAGENAN KAPAL ASING (PKKA) PADA PT YANG MING SHIPPING INDONESIA - Andri Primadi; Prena Ramadhita Kurniawan (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to analyze the process of issuing the Ship Agency Approval (PKKA) document using the SIMLALA application at PT. Yang Ming Shipping Indonesia and to identify the challenges faced in the system’s implementation. The research method which includes observation and interviews with the implementers and supervisors in the company, along with library research by reviewing relevant literature. The findings reveal that the issuance of PKKA through SIMLALA involves several steps, such as data entry, document uploading, and verification by the relevant authorities. Although designed to expedite administrative processes, challenges such as data entry errors, limited operational hours of the system, and document revisions often hinder the smooth issuance of PKKA. Effective coordination between the company and relevant authorities is essential to enhance the efficiency of this system.